Collection and processing of bearing vibration data for their technical condition classification by machine learning methods - Babudzhan, Ruslan; Isaienkov, Kostiantyn; Krasii, Danylo; Melkonian, Ruben; Vodka, Oleksii; Zadorozhniy, Ivan; Yushchuk, Michael (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2021)
An experimental research facility has been developed to receive vibration signals from mechanisms with installed rolling bearings. A control block for all equipment has been created. For the repeatability of the experiment, an external microcontroller with a programmed proportional-integral-derivative regulator was used. Experiments were carried out to obtain initial data for different types of bearings. The processed data were grouped and made publicly available for further research. It is proposed to solve the problem of emergency stop of the generator, arising during operation due to bearings worn, by recognizing the pre-emergency conditions of rotary rig based on the use of advanced machine learning techniques: to highlight the signs of vibration and build clusters according to the degree of worn.